Learning through reflection as part of a DPS programme - Papadima-Sophocleous, Salomi (My University, 2006)
This paper describes the benefits of reflective learning as part of a work-based doctorate study programme. The paper is presented in two sections: The first provides an extended framework for reflective learning. The second is an account of my own reflective learning based within my academic context as work-based doctorate student and my professional context as a creator and writer of the New English Placement Test Online for Intercollege, a private tertiary educational institution where I work.
Keywords: English Placement Test Online; Doctorate Study Programme